(untitled) (Research, Society and Development, 2022)
A relatively recent sequence of interventions investigating, in addition to anthropometric characteristics, dermatoglyphics in bodybuilding has been presented in science databases. In most cases, the female categories of this sport have been investigated, but no competitors at the professional level have been reached, which requires, for the initial findings to be confirmed, that subsequent interventions consider the level of the athletes, as well as the time of exposure to the rigors of high performance. Objective: Our goal was to carry out a dermatoglyphic, somatotypical, and anthropometric investigation, observing the level and time of competitive activity. Methodology: This is a case study, which had as volunteer a bodybuilder with expressive titles in this sport, obtained during a long-lasting career. Results: Although the anthropometric evaluation was carried out in the off-season period, the adipose, muscular and bone components presented the classifications in very low, very high and within normality; the somatotype was classified as Endomorphic Mesomorphic, being the endomorphy lower than the average of a sample with bodybuilders who participated in one of the Brazilian championships; the dermatoglyphic classification pointed to an eminence of glycolytic fibers, with type IIa standing out. Conclusion: We conclude, when evaluating a high-level bodybuilder, that a higher conditioning than the reference used, found in our survey, was presented; and that the dermatoglyphics corresponded, similarly to previous findings, to the requirements of the division investigated.